2009
DOI: 10.1016/j.nut.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Low protein diet changes the energetic balance and sympathetic activity in brown adipose tissue of growing rats

Abstract: Protein restriction led to an increase in EE, with probable activation of thermogenesis in brown adipose tissue, evidenced by an increase in catecholamines levels. Despite the higher EE, energetic gain and lipids increased. The high level of leptin associated with hyperphagia led to the supposition that these animals are leptin resistant, and the increase in insulin sensitivity, suggested by the relation between insulin and glycemia in fasting and fed animals, might contribute to lipid accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 35 publications
20
52
1
Order By: Relevance
“…The hypophagic effect of protein-free diets, and hyperphagic effect of very low protein and moderately low protein diets, in the current study are consistent with the 'protein leverage' hypothesis 2 , as well as previous studies on protein restriction in rats, mice and humans 1,[6][7][8][9]14,17,22 . Although the low protein-induced hyperphagia is associated with a central orexigenic drive 11,[15][16][17][18] , the peripheral signals that transmit information to central neural networks are poorly defined.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The hypophagic effect of protein-free diets, and hyperphagic effect of very low protein and moderately low protein diets, in the current study are consistent with the 'protein leverage' hypothesis 2 , as well as previous studies on protein restriction in rats, mice and humans 1,[6][7][8][9]14,17,22 . Although the low protein-induced hyperphagia is associated with a central orexigenic drive 11,[15][16][17][18] , the peripheral signals that transmit information to central neural networks are poorly defined.…”
Section: Discussionsupporting
confidence: 91%
“…Despite an initial increase in energy expenditure, this effect did not persist in the 0P likely due to the sustained anorexia and weight loss. Previous studies have shown that an increased sympathetic influx to BAT is required for the thermogenic effects of low protein diets [19][20][21][22][23] . In the present study, using propranolol, a β -AR antagonist, we demonstrate that energy expenditure was dose-dependently attenuated in animals fed low protein diets with maximal attenuation in protein deprived rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data from our laboratory observed that growing rats fed a low-protein, high-carbohydrate diet (LPHC diet: 6% protein, 74% carbohydrate) for 15 days showed a decrease in the body mass gain, despite the increase in food and calorie intakes and the increased lipid content in the carcass and in white and brown adipose tissues, by comparison with rats fed a control diet (C diet: 17% protein, 63% carbohydrate); the lowest mass gain for LPHC-fed rats was attributed, at least in part, to a decrease in the mass of the skeletal muscles (Aparecida de França et al 2009). A few studies have described the changes in skeletal muscle protein metabolism induced by adaptation to an LPHC diet ; however, the contribution of specific components of the different proteolytic systems to the control of muscle mass and the biochemical mechanisms underlying the reduced rate of skeletal muscle protein synthesis and breakdown under conditions of dietary protein deficiency remain unclear.…”
Section: Introductionmentioning
confidence: 88%